THE INFLUENCE OF THE PHYSICAL WORK ENVIRONMENT AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE - Liawati Liawati; Dodi Prasada; Tutri Indraswari (Asosiasi Dosen Muda Indonesia, 2024)
This research explores the impact of the physical work environment and career development on employee performance at CV. Ide Creative Printing Tangerang Selatan. The research uses a quantitative approach for all CV employees. South Tangerang Creative Printing Idea, totaling 60 people, was used as the research population. Data collection methods include observation, literature study, and use of questionnaires. Data analysis was carried out using various statistical tests, such as Validity Test, Reliability, Classical Assumptions, Pearson Correlation, Determination, Simple Linear Regression, and Hypothesis Testing. The analysis results show that the physical work environment and career development significantly influence employee performance at CV. Ide Creative Printing Tangerang Selatan. The multiple linear regression value shows the positive contribution of these two variables to employee performance, with a contribution of 67.3%, while other factors influence the remaining 32.7%.